The Conceptualization of Legal Harmonization Approach in Malaysia - Mohamad Ismail Bin Mohamad Yunus (Fiat Justisia, 2023)
The term "harmonization," derived from "harmony," encompasses various meanings. In the context of this discussion, it refers to the willingness and openness to recognize, acknowledge, adopt, or accept elements produced by man-made laws, modern secular traditions, customs, cultures, and institutions that are perceived to align with or not contradict the worldview, principles, values, teachings, and norms of Islam. Therefore, the conceptual approach to harmonizing legal knowledge and education is a process of actualizing divine imperatives within the legal sphere. Legal harmonization is a fundamental concept in comparative law that has gained prominence on both international and national agendas over the past decade. In Malaysia, numerous efforts have been made to identify similarities among legal rules across different jurisdictions; however, these efforts have faced challenges due to a lack of comprehensive understanding regarding the nature and scope of harmonization. This article examines various dimensions of harmonization, treating it as a legal phenomenon rather than merely a process of drafting similar rules. A thorough understanding of harmonization as a legal phenomenon can enhance the evaluation of implementation processes and inform the formulation of new legal initiatives.